Perakitan Sensor Asap Pada Alat Penyaring Asap Untuk Mengontrol Fan Secara Otomatis - Rozy Aditya Wiratama; Rakiman Rakiman; Eka Sunitra (Politeknik Negeri Padang, 2019)
Starting from the events on the island of Sumatra that often experience forest fires and result in the emergence of smog that can disrupt the respiratory tract in living things, especially in humans. Thus resulting in the emergence of diseases such as ispa, shortness of breath, and other diseases. This is caused by polluted air because the concentration of oxygen (O2) is only a few percent compared to air containing carbon dioxide (CO2), carbon monoxide (CO), sulfide (S2) and other combustion substances. The smoke sensor is useful for activating the fan on the smoke filter tool automatically, the Fan functions as a smoke suction to be forwarded to the room where the smoke is filtered. The workings of this tool are, when the sensor reads the smoke content on the tool more than 140 ppm, then the relay connected to the fan will activate and make the fan spin. After the fan or fan lives, then the smoke will be sucked into a tube, where the tube has a small hose at the end, then the smoke is released at the end of the hose, where the end of the hose is soaked in a container containing water, where the air will be filtered. The results of the filter are sucked back by the fan or fan in another room. If the smoke level has fallen below the threshold of 140 ppm, the fan will automatically die.